2012
DOI: 10.4049/jimmunol.1101405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Systemic versus Local Administration of Corticosteroids on Mucosal Tolerance

Abstract: Respiratory exposure to allergen induces T cell tolerance and protection against the development of airway hyperactivity in animal models of asthma. Whereas systemic administration of dexamethasone during the delivery of respiratory Ag has been suggested to prevent the development of mucosal tolerance, the effects of local administration of corticosteroids, first-line treatment for patients with bronchial asthma, on mucosal tolerance remain unknown. To analyze the effects of systemic versus local administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…The immunosuppressant and anti-inflammatory properties of corticosteroids are well established ( 45 , 46 ). A recent study ( 47 ) revealed that the systemic rather than the topical administration influences the mucosal tolerance. The authors concluded that the route of administration rather than the doses of corticosteroids administered affects the immune response, this finding being in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressant and anti-inflammatory properties of corticosteroids are well established ( 45 , 46 ). A recent study ( 47 ) revealed that the systemic rather than the topical administration influences the mucosal tolerance. The authors concluded that the route of administration rather than the doses of corticosteroids administered affects the immune response, this finding being in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of corticosteroids was reported to inhibit respiratory tolerance [43] and to permanently amplify the Th2 responses [44]. Dendritic cells from corticosteroid-treated mice have been shown to be unable to transfer respiratory tolerance or induce Treg cells [45]. Therefore, GC released upon stress exposure might bias immune regulation preferentially towards a Th2 response in response to a specific antigen, thereby eventually aggravating asthmatic responses to antigen challenges subsequent to stress exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GC treatment during antigen inhalation to promote the development of respiratory tolerance was shown to eliminate IL-10-producing dendritic cells, which are required for the development of IL-10-producing Treg cells, leading to Th2-biased sensitization and allergic airway responses upon antigen exposure (Stock et al 2005). Interestingly, the development of respiratory tolerance was shown to be prevented by systemic, but not local, GC administration (Kerzerho et al 2012), in accordance with our finding that respiratory tolerance was inhibited in mice that showed increased blood GC levels in response to stress exposure (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%